The moral veto : framing contraception, abortion, and cultural pluralism in the United States - Burns, Gene, 1958- (Cambridge University Press, 2005)
Based on archival and sociological research, and speaking to issues in the study of culture, social movements, and legal change, The Moral Veto: Framing Contraception, Abortion, and Cultural Pluralism in the United States examines the often surprising history of controversies over contraception and abortion.